The effect of e-WOM, usefulness, and ease of use on attitude towards using the PLN mobile application with trust as a mediation variable - Ummul Fadhilah; Rahmiati Rahmiati; Khairen Niza Mefid; Ahmad Istiqlal Ahlunnazak (Universitas Negeri Padang, 2023)
This study aims to analyze the extent to which E-wom, usefulness, and ease of use on Attitude Towards Using the PLN Mobile application through the rust variable as a mediating variable. The population in this study were all users of the PLN Mobile application. The sample in this study was 385 respondents using a purposive sampling method. The analytical technique used is SEM analysis using smart PLS3. The results of this study indicate that e-wom, usefulness, and ease of use provide a significant direct influence on the trust variable and the attitude towards using a variable. The results of this study also found that trust has a direct and significant influence on attitude towards using. The results of this study explain that the trust variable is able to provide a mediating role on the effect of e-wom and its usefulness on attitude toward using. However, trust cannot be a mediating variable on the effect of ease of use on attitude toward using.